2022
DOI: 10.1186/s13104-022-06247-1
|View full text |Cite
|
Sign up to set email alerts
|

Daytime fluctuations of endurance performance in young soccer players: a randomized cross-over trial

Abstract: Objectives Fluctuations of physical performance and biological responses during a repetitive daily 24-h cycle are known as circadian rhythms. These circadian rhythms can influence the optimal time of day for endurance performance and related parameters which can be crucial in a variety of sports disciplines. The current study aimed to evaluate the daytime variations in endurance running performance in a 3.000-m field run and endurance running performance, blood lactate levels, and heart rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, results from previous studies have shown similar or higher differences for other treadmill models (de Groot et al, 2006). The differences found in both studies are much higher than an expected error of measurement or the daily performance fluctuation (Fiedler et al, 2022). Thus, beside the regular quality management routine of an exercise testing laboratory and stable environmental conditions (temperature, humidity) it is highly recommended to keep also an eye on the athletes' equipment and to use always the same tire pressure.…”
Section: Practical Implicationsmentioning
confidence: 67%
See 1 more Smart Citation
“…However, results from previous studies have shown similar or higher differences for other treadmill models (de Groot et al, 2006). The differences found in both studies are much higher than an expected error of measurement or the daily performance fluctuation (Fiedler et al, 2022). Thus, beside the regular quality management routine of an exercise testing laboratory and stable environmental conditions (temperature, humidity) it is highly recommended to keep also an eye on the athletes' equipment and to use always the same tire pressure.…”
Section: Practical Implicationsmentioning
confidence: 67%
“…Especially in elite sports, such characteristics are of utmost interest to detect minimal performance differences, as small time differences of less than 0.5% of the racing time decide over winning or losing a medal at international championships, such as Paralympic Games (Perret, 2017). Typical diurnal fluctuations of performance are commonly at around 1% of the time trial performance (Fiedler et al, 2022).…”
Section: Introductionmentioning
confidence: 99%